Progression Toward Decompensated Right Ventricular Failure in the Ovine Pulmonary Hypertension Model. Issue 2 (20th April 2021) - Ukita, Rei; Tumen, Andrew; Stokes, John W.; Pinelli, Christopher; Finnie, Kelsey R.; Talackine, Jennifer; Cardwell, Nancy L.; Wu, W. Kelly; Patel, Yatrik; Tsai, Emily J.; Rosenzweig, Erika B.; Cook, Keith E.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Decompensated right ventricular failure (RVF) in patients with pulmonary hypertension (PH) is fatal, with limited treatment options. Novel mechanical circulatory support systems have therapeutic potential for RVF, but the development of these devices requires a large animal disease model that replicates the pathophysiology observed in humans. We previously reported an effective disease model of PH in sheep through ligation of the left pulmonary artery (PA) and progressive occlusion of the main PA. Herein, we report a case of acute decompensation with this model of chronic RVF. Gradual PA banding raised the RV pressure (maximum RV systolic/mean pressure = 95 mmHg/56 mmHg). Clinical findings and laboratory serum parameters suggested appropriate physiologic compensation for 7 weeks. However, mixed venous saturation declined precipitously on week 7, and creatinine increased markedly on week 9. By the 10th week, the animal developed dependent, subcutaneous edema. Subsequently, the animal expired during the induction of general anesthesia. Post-mortem evaluation revealed several liters of pleural effusion and ascites, RV dilatation, eccentric RV hypertrophy, and myocardial fibrosis. The presented case supports this model's relevance to the human pathophysiology of RVF secondary to PH and its value in the development of novel devices, therapeutics, and interventions.